OPTIMIZATION OF GRAPHENE/TiO2 PHOTOELECTRODE FOR EFFICIENT DYE-SENSITIZED SOLAR CELL - SHAHID , MUHAMMAD UMAIR (2020)
Dye solar cells (DSCs) have emerged as a promising alternative to the conventional silicon solar cells due to the ease of fabrication, low-cost, and working ability in diffuse light